Clinical Studies of Nonpharmacological Methods to Minimize Salivary Gland Damage after Radioiodine Therapy of Differentiated Thyroid Carcinoma: Systematic Review - Christou, Andri; Papastavrou, Evridiki; Merkouris, Anastasios; Frangos, Savvas; Tamana, Panayiota; Charalambous, Andreas (My University, 2016)
Purpose. To systematically review clinical studies examining the effectiveness of nonpharmacological methods to prevent/minimize salivary gland damage due to radioiodine treatment of differentiated thyroid carcinoma (DTC). Methods. Reports on relevant trials were identified by searching the PubMed, CINHAL, Cochrane, and Scopus electronic databases covering the period 01/2000-10/2015. Inclusion/exclusion criteria were prespecified. Search yielded eight studies that were reviewed by four of the present authors. Results. Nonpharmacological methods used in trials may reduce salivary gland damage induced by radioiodine. Sialogogues such as lemon candy, vitamin E, lemon juice, and lemon slice reduced such damage significantly (p < 0.0001, p < 0.05, p < 0.10, and p < 0.05, resp.). Parotid gland massage also reduced the salivary damage significantly (p < 0.001). Additionally, vitamin C had some limited effect (p = 0.37), whereas no effect was present in the case of chewing gum (p = 0.99). Conclusion. The review showed that, among nonpharmacological interventions, sialogogues and parotid gland massage had the greatest impact on reducing salivary damage induced by radioiodine therapy of DTC. However, the studies retrieved were limited in number, sample size, strength of evidence, and generalizability. More randomized controlled trials of these methods with multicenter scope and larger sample sizes will provide more systematic and reliable results allowing more definitive conclusions.
Keywords: Nonpharmacological methods; Salivary gland damage; Radioiodine treatment; Thyroid carcinoma